(untitled) (Colombia Medica, 2023)
Case description: 42-year-old woman with severe pulmonary and mediastinal inflammatory involvement, secondary to infiltration of a silicone-related allogenic material with systemic migration. Clinical findings: The patient developed esophageal and bronchial stenosis, recurrent infections, malnutrition, and respiratory deterioration, making surgical removal of the allogenic material impossible. Treatment and outcome: Clinical and radiological improvement was achieved after treatment with multiple intravenous and oral immunomodulators. Clinical relevance: Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) is a heterogeneous disease that results from exposure to allogenic substances in a subject with genetic susceptibility. These substances induce autoimmune or autoinflammatory phenomena. ASIA was recently described, and its diagnostic criteria are still under discussion. The prognosis of this syndrome is not clear, and its treatment is based on the elimination of the causing substance; however, this often does not improve the patient’s condition, and it is necessary to initiate immunomodulatory treatment. The treatment used in this patient was not previously described in the literature.